Food Safety Resources - Oyarzabal, Omar A.; Backert, Steffen (Microbial Food Safety, 2011)
There are several food safety resources available in the form of books, journals, trade magazines, and, more recently, through the Internet. This chapter briefly summarizes, in table format, most of the available resources that can provide complementary reading to the chapters described in this book. The summary starts with the books that deal mainly with food safety (Table 1), continues with other microbiology books with sections that deal with food safety (Table 2), moves on to list refereed-journal magazines related to food safety (Table 3), and finally provides some Internet resources related to food safety (Table 4).<br
Keywords: Food Safety; Trade Magazines; Table Format; Microbiology; Important Repository